Open Reading Frame 1a-Encoded Subunits of the Arterivirus Replicase Induce Endoplasmic Reticulum-Derived Double-Membrane Vesicles Which Carry the Viral Replication Complex - Pedersen, Ketil W. (American Society for Microbiology, 1999)
The replicase of equine arteritis virus (EAV; family Arteriviridae, order Nidovirales) is expressed in the form of two polyproteins (the open reading frame 1a [ORF1a] and ORF1ab proteins). Three viral proteases cleave these precursors into 12 nonstructural proteins, which direct both genome replication and subgenomic mRNA transcription. Immunofluorescence assays showed that most EAV replicase subunits localize to membranes in the perinuclear region of the infected cell. Using replicase-specific antibodies and cryoimmunoelectron microscopy, unusual double-membrane vesicles (DMVs) were identified as the probable site of EAV RNA synthesis. These DMVs were previously observed in cells infected with different arteriviruses but were never implicated in viral RNA synthesis. Extensive electron microscopic analysis showed that they appear to be derived from paired endoplasmic reticulum membranes and that they are most likely formed by protrusion and detachment of vesicular structures with a double membrane. Interestingly, very similar membrane rearrangements were observed upon expression of ORF1a-encoded replicase subunits nsp2 to nsp7 from an alphavirus-based expression vector. Apparently, the formation of a membrane-bound scaffold for the replication complex is a distinct step in the arterivirus life cycle, which is directed by the ORF1a protein and does not depend on other viral proteins and/or EAV-specific RNA synthesis.